2018
DOI: 10.1007/s00590-018-2228-5
|View full text |Cite
|
Sign up to set email alerts
|

Wrist hemiarthroplasty for irreparable DRF in the elderly

Abstract: Our data suggest that treatment of acute irreparable distal radius fracture in the independent elderly patient with a bone-preserving primary wrist hemiarthroplasty may be a viable option. Longer-term follow-up are needed to confirm these preliminary data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 17 publications
1
9
0
2
Order By: Relevance
“…Recent studies showed moderate results for wrist hemiarthroplasty in elderly patients following complex DRF [11][12][13][14][15][16][17][18][19][20]. The idea of hemiarthroplasty for this indication was first implemented by Roux in 2005 [11].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent studies showed moderate results for wrist hemiarthroplasty in elderly patients following complex DRF [11][12][13][14][15][16][17][18][19][20]. The idea of hemiarthroplasty for this indication was first implemented by Roux in 2005 [11].…”
Section: Discussionmentioning
confidence: 99%
“…In 2015, Herzberg [ 12 ] reported first results of the Cobra prosthesis for complex DRFs, which is also more bone sparing and does not require an intact distal ulna compared to the SOPHIA implant. His experiences have been described in several publications [ 12 , 13 , 18 ]. A direct comparison to our current data is limited, as the authors combine the results of the Cobra implant with the radial component of the Press-fit-Remotion Total Wrist implant (Small Bone Innovations, Morrsiville, PA, USA) [ 12 , 13 , 18 ] (Table 6 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Falls die knöchernen Fragmente der "sigmoid notch" zusammengeführt, vernäht und erhalten werden können, bleibt der Ulnakopf intakt und das distale Radioulnargelenk gerettet. Falls die knöchernen Fragmente der "sig-moid notch" nicht rekonstruierbar sind oder falls eine Ulnakopf-oder -halsfraktur vorliegt, wird der Ulnakopf nach Watson schräg reseziert [10,11]. Der Ulnastumpf wird durch transossäre Nähte der palmaren Kapsel des distalen Radioulnargelenks mit dem dorsalen Anteil des Ulnarstumpfes nach Blatt stabilisiert.…”
unclassified